Effect of magnetic field on nanofluid free convection in Conical Partially Annular Space - AISSA Abderrahmane; Amine MEDEBBER Mohamed; Al-Farhany Khaled; SAHNOUN Mohammed; Khaleel Kareem Ali; EL GANAOUI Mohammed (MATEC Web of Conferences, 2020)
Natural convection of a magneto hydrodynamic nanofluid in a porous cavity in the presence of a magnetic field is investigated. The two vertical side walls are held isothermally at temperatures Th and Tc, while the horizontal walls of the outer cone are adiabatic. The governing equations obtained with the Boussinesq approximation are solved using Comsol Multiphysics finite element analysis and simulation software. Impact of Rayleigh number (Ra), Hartmann number (Ha) and nanofluid volume fraction (ϕ) are depicted. Results indicated that temperature gradient increases considerably with enhance of Ra and ϕ but it reduces with increases of Ha.